Gender and age differences in the risk of allergic reactions following the Pfizer-BioNTech COVID-19 and AstraZeneca vaccine using skin prick test and intradermal test among patients with high risk for hypersensitivity - Svarça, Leonora; Bojadzieva, Sonja; Rashiti, Premtim; Rashiti-Bytyçi, Albiona; Kabashi, Diar (Allergologia et Immunopathologia, 2025)
Objective: The aim of this study was to assess the association between allergic reactions after COVID-19 vaccination and the history of high-risk allergy, individual predisposing factors such as age and gender, and COVID-19 vaccine type.Materials and methods: This retrospective cohort study included 234 adult patients (18 years old and above) who underwent a COVID-19 vaccine allergy test up until February 2023 in a Clinic of Allergy and Clinical Immunology in the University Clinical Center of Kosovo. All patients suspected of allergy underwent skin testing: SPT (skin prick test) and IDT (intradermal test) using either an mRNA (ribonucleic messenger acid) vaccine (BNT162b2, Pfizer-BioNTech) and/or an adenoviral vector vaccine (AZD1222, AstraZeneca). Subsequent immunization was administered under careful medical observation.Results: Among the 234 patients with a high-risk allergy profile, several potential risk factors were identified, including a history of multiple allergies, previous anaphylaxis, and/or drug allergies. In our cohort, food allergies were reported by 20 patients (8.5%) and multiple drug allergies were reported by 118 patients (50.4%). Due to the retrospective nature of the study, we cannot establish causality. Therefore, older age and receipt of the Pfizer-BioNTech vaccine were found to be associated with increased allergic reactions after COVID-19 vaccination, while male gender was associated with decreased risk. Although previous allergic manifestations were common among those with reactions, they were not significantly associated with increased risk after adjustment for confounders. The absence of a control group consisting of vaccinated individuals without a high-risk allergy history limits the generalizability of our findings.Conclusions: Immediate allergic reactions to COVID-19 vaccines are rare but can be severe and reoccur. Findings suggest that gender and age-specific factors may influence the response to the vaccine. Nevertheless, COVID-19 vaccines remain a critical tool in preventing severe disease and controlling the ongoing pandemic.